Accuracy of Digital Radiography and Cone Beam Computed Tomography on Periapical Radiolucency Detection in Endodontically Treated Teeth - Tadas Venskutonis; Povilas Daugela; Marijus Strazdas; Gintaras Juodzbalys (eJournal of Oral Maxillofacial Research)
Objectives: The aim of the present study was to compare the accuracy of intraoral digital periapical radiography and cone beam computed tomography in the detection of periapical radiolucencies in endodontically treated teeth.